Rasio Interval Training Dalam Latihan Shadow Bulutangkis Terhadap Power dan Kecepatan - Himawan Wismanadi; Fatkur Rohman Kafrawi; Made Pramono; Awang Firmansyah; Afif Rusdiawan (Journal Sport Area, 2020)
Speed ​​and power are the most important physical components in badminton with the current rally point system. The purpose of this study was to determine the effect of badminton shadow training on power and speed. This research used experimental research with randomized group pre-test and post-test design. The subjects of this study were male students IKOR unesa 2018 class which were randomly divided into experimental group 1 (K1) and experimental group 2 (K2) consisting of 10 people per group. K1 group was given badminton shadow training with 1: 1 interval training method and K2 group with 1: ½ interval training method with 15 seconds training time. The power test is performed using jump MD and the speed test is carried out with a 30 Meter sprint test. Paired t test results were significant (p <0.05) on power (p = 0.035) and speed (p = 0.006) at K1, whereas at K2 were also significant at power (p = 0,000) and speed (p = 0.014). Independent sample t test results were not significant at the power (p = 0.190), while the speed was also not significant (p = 0.165). In conclusion, badminton shadow training can increase power and speed with both 1:1 or 1: ½ interval training ratios. Shadow badminton training with 1: ½ interval training is more to increase power and speed because on average the results are better than shadow badminton training with 1:1 interval training.